Diplomacy : theory and practice - Berridge, Geoff (2015)
"This revised fifth edition of the bestselling Diplomacy, from globally renowned thinker and scholar in diplomacy research and teaching Geoff Berridge, takes into account crucial developments and shifts on the global stage in the last 5 years. At the heart of diplomacy, and a central theme of this book, is the art of negotiation. As well as involving choice of its most promising channels, this includes how to sustain momentum via a deadline, for the consequences of not settling by midnight on the clock of the talks usually concentrates minds. The examples included, such as the Iran nuclear talks, are mostly contemporary, but historical background to the diplomatic methods themselves is always provided. This helps to show that a rejuvenation of key features of traditional diplomacy has occurred in recent years that has gone largely unnoticed, partly because new labels have been given to old procedures, a notable instance being the rebranding of propaganda as 'public diplomacy'. Fully updated, new case studies explore lessons of the 2014 G20 summit in Brisbane, and those of the highly topical Budapest Memorandum on Ukraine. Berridge's comprehensive and invaluable text also includes new chapters on secret intelligence and economic and commercial diplomacy"--
Machine generated contents note: -- Introduction -- 1. The Foreign Ministry -- Staffing And Supporting Missions Abroad -- Policy-Making And Implementation -- Coordination Of Foreign Relations -- Dealing With Foreign Diplomats At Home -- Building Support At Home -- PART I: THE ART OF NEGOTIATION -- Introduction To Part I -- 2. Prenegotiations -- Agreeing The Need To Negotiate -- Agreeing The Agenda -- Agreeing Procedure -- 3.'Around-The-Table' Negotiations -- The Formula Stage -- The Details Stage -- 4. Diplomatic Momentum -- Deadlines -- Metaphors Of Movement -- Publicity -- Raising The Level Of The Talks -- 5. Packaging Agreements -- International Legal Obligations At A Premium -- Signalling Importance At A Premium -- Convenience At A Premium -- Saving Face At A Premium -- 6. Following Up -- Early Methods -- Monitoring By Experts -- Monitoring By Embassies -- Review Meetings -- PART II: DIPLOMATIC RELATIONS -- Introduction To Part II -- 7. Telecommunications -- Telephone Diplomacy Flourishes -- Video-Conferencing Stutters -- Other Means Multiply -- 8. Embassies -- The Normal Embassy -- The Fortress Embassy -- The Mini-Embassy -- The Militarized Embassy -- 9. Consulates -- Consular Functions -- Career Consuls -- Honorary Consuls -- Consular Sections -- 10. Secret Intelligence -- Service Attache;s -- Intelligence Officers -- Cuckoos In The Nest? -- 11. Conferences -- International Organizations -- Procedure -- 12. Summits -- Professional Anathemas -- General Case For The Defence -- Serial Summits -- Ad Hoc Summits -- The High-Level Exchange Of Views -- 13. Public Diplomacy -- Rebranding Propaganda -- The Importance Of Public Diplomacy -- The Role Of The Foreign Ministry -- The Role Of The Embassy -- 14. Economic And Commercial Diplomacy -- Rising Priorities -- Multilateralism And The Squeeze On The Foreign Ministry -- Embassy Tasks And Set-Up -- PART III: DIPLOMACY WITHOUT DIPLOMATIC RELATIONS -- Introduction To Part III -- 15. Disguised 'Embassies' -- Interests Sections -- Consulates -- Representative Offices -- Front Missions -- 16. Special Missions -- The Advantages Of Special Missions -- The Variety Of Special Missions -- To Go Secretly Or Openly? -- 17. Mediation -- The Nature Of Mediation -- Different Mediators And Different Motives -- The Ideal Mediator -- The Ripe Moment -- Conclusion.
Includes bibliographical references (pages 269-279) and index.
Keywords: Diplomacy; POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / International Relations / Diplomacy; POLITICAL SCIENCE / International Relations / Treaties